2021
DOI: 10.1002/celc.202101141
|View full text |Cite
|
Sign up to set email alerts
|

Operando Local pH Mapping of Electrochemical and Bioelectrochemical Reactions Occurring at an Electrode Surface: Effect of the Buffer Concentration

Abstract: In this study, we aim at demonstrating the possibility for operando quantification of the thickness of the boundary layer where pH changes are occurring upon electrochemical reactions accompanied with the production or consumption of H + cations. Confocal fluorescent microscopy (CFM) is combined with two different pH sensitive fluorescent dyes, namely 3,4'dihydroxy-3',5'-bis-(dimethylaminomethyl)flavone (FAM345) and rhodamine-6-aniline (R6H). This is the first attempt to quantify the effect of the buffer conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…The use of the pH-switchable reversible complex formation of the nitro-avidin-biotin or avidin-iminobiotin systems can further benefit from another research direction, which provides reversible pH changes near electrode surfaces upon performing some electrochemical reactions. 26 The local (interfacial) pH change has been already used to control electrochemically activity of surface-immobilized enzymes 27 and to release molecular loads bound to an electrode surface, 28 particularly with pH-degradable covalent bonds. 29 The present paper reports on the use of electrode-surface immobilized nitro-avidin or avidin in combination with biotinylated or iminobiotinylated substances, respectively, with the local pH changes produced electrochemically.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The use of the pH-switchable reversible complex formation of the nitro-avidin-biotin or avidin-iminobiotin systems can further benefit from another research direction, which provides reversible pH changes near electrode surfaces upon performing some electrochemical reactions. 26 The local (interfacial) pH change has been already used to control electrochemically activity of surface-immobilized enzymes 27 and to release molecular loads bound to an electrode surface, 28 particularly with pH-degradable covalent bonds. 29 The present paper reports on the use of electrode-surface immobilized nitro-avidin or avidin in combination with biotinylated or iminobiotinylated substances, respectively, with the local pH changes produced electrochemically.…”
mentioning
confidence: 99%
“…It has been already shown that the electrochemical reduction of O 2 results in pH increase near an electrode surface. 26,28 Indeed, the electrochemical oxygen reduction leading to H 2 O 2 or H 2 O production (depending on the potential applied and the electrode material) results in consumption of H + ions, thus, producing the H + depletion near the electrode surface and the pH increase. This results in the dissociation of the nitro-avidin-biotin complex and release of the biotinylated fluorescent dye, then detected in a bulk solution by fluorescence measurements.…”
mentioning
confidence: 99%
See 3 more Smart Citations